Bioetanol dari Limbah Sekam Padi sebagai Sumber Energi Terbarukan - Intan Farhani; Indah Sawitri; Pramita Desi Hariningsih; Ida Farida; Omay Sumarna (Jurnal Engine: Energi, Manufaktur, dan Material, 2025)
The purpose of this research is to make laboratory-scale bioethanol from agroindustrial waste, namely rice husk through hydrolysis, fermentation, and distillation methods, determine %yield, and characterize bioethanol. The method used was experimental. The results and conclusions obtained are bioethanol that smells like tape, colorless with %yield as much as 3,32%, density of 0.8818 g/mL, viscosity of 0.7408 cP, and blue flame formed during the flame test. Based on the characterization results, the bioethanol obtained has not met the SNI standards, which is suspected because it still contains water content caused by less pure ethanol from the distillation process.